ANALISIS CELAH KEAMANAN JARINGAN MENGGUNAKAN PENGUJIAN INTRUTION DETECTION SYSTEM DAN MICROSOFT NETWORK MONITOR - Aliy Hafiz; Sukatmi . (Jurnal informasi dan komputer, 2022)
Cybercrime today deserves the attention of all parties carefully. Using IDS and Network Monitoring applications such as Microsoft Network Monitor can detect attacks targeting servers. Attack prevention with anomaly detection is by comparing the network traffic being monitored with network traffic that usually occurs. With this capability Snort can simplify the handling of computer network security.